Kerusakan Antropogenik dalam Ekosistem Hutan Cot Girek Anthropogenic Damage in the Cot Girek Forest Ecosystem - Darmadi Darmadi; Usman Pelly; Deny Setiawan (Program Studi Antropologi Sosial Pascasarjana Universitas Negeri Medan, 2018)
This study discusses anthropogenic activity issues in the area of Cut Mutia protected forest in Cot Girek District, North Aceh Regency, Aceh Province. The purpose of this study is to get an overview of illegal logging practices, patterns of action and the impacts caused by these anthropogenic practices. This research is a descriptive qualitative research, using a Progressive Contextualization approach. The results of this study indicate that anthropogenic activities found in the Cot Girek protected forest area are PT Bandum Payah Tamita (MPT)’s HGU concessions and the illegal logging practices are carried out in an organized and systematic manner. PT MPT's HGU activities have been rejected by the community since they may cause ecological damage to the Cot Girek forest ecosystem. The group of illegal loggers use a tiered network with each role from upstream to downstream to run an illegal timber business. In conclusion, anthropogenic practices are carried out on a massive and exploitative basis causing deforestation, destruction of animal habitats, human and animal conflicts, and natural disasters.